Dynamic Performance Analysis of Uplink Transmission in Cluster-Based Heterogeneous Vehicular Networks - Qiang Zheng; Kan Zheng; Liang Sun; Leung, Victor C. M. (IEEE transactions on vehicular technology, 2015)
As an emerging technology, vehicular networks have evolved into an indispensable part of intelligent transport systems (ITS). Thus, this paper focuses on the performance analysis of the cluster-based heterogeneous vehicular networks (C-HetVNETs) with dynamic data arrival rate and different vehicle densities. Different from the previous studies, which mainly focus on network capacity in just one wireless-technology-supported vehicular network, such as dedicated short-range communication (DSRC) or Third-Generation Partnership Project (3GPP) long-term evolution (LTE), we focus on the different performance metrics of uplink transmission in C-HetVNET. First, we develop a framework of C-HetVNET by employing the cluster mechanism. Then, the performance analysis models of intracluster and intercluster communications are designed based on a Markov queuing model. Due to the explosion of state space, model decomposition and iteration techniques are proposed to handle this problem. Based on the developed analytical model, the performance metrics of different scheduling schemes, in terms of throughput, delay, dropping probability, and queue length, are studied and compared. The performances of C-HetVNETs under different vehicle densities and data arrival rates are obtained via analysis and simulations, which give a useful guideline for network configuration of C-HetVNETs. The proposed analytical model can be also used for heterogeneous or two-tier network analysis and validation of network simulators under various traffic conditions. In addition, we investigate the performances of LTE networks used for vehicular communications for the purpose of performance comparison.